Analysis of the epidemiological profile of syphilis in pregnant women in the municipality of Maceió (Research, Society and Development, 2025)
The present study aimed to analyze the epidemiological profile of syphilis in pregnant women in the municipality of Maceió, from 2020 to 2024. This is a descriptive study, based on secondary data from the Notifiable Diseases Information System (SINAN). The results pointed to a progressive increase in cases between 2020 and 2023, with a peak in 2023, followed by a slight reduction in 2024. This behavior may be related to the expansion of testing and notification actions, as well as the implementation of public policies aimed at prevention and early diagnosis. A higher prevalence was observed among brown pregnant women living in urban areas, which reflects social and racial inequalities in access to health services. The low occurrence among indigenous and Asian pregnant women is possibly due to underreporting and barriers in access to prenatal care. The expressive proportion of records with incomplete information is also noteworthy, indicating weaknesses in the epidemiological surveillance system. It is concluded that the fight against syphilis in pregnant women requires the strengthening of testing, treatment and notification actions, in addition to expanding access to quality prenatal care, aiming to reduce vertical transmission and the impacts on maternal and child health.